Environment-friendly anti-softening treatment ironing and dyeing printing method for baby lint fabric
Through environmentally friendly anti-soft finishing liquid and advanced dyeing and fixing technology, the safety hazards caused by formaldehyde and organic halogen compounds in baby flannel fabrics are solved, efficient anti-soft treatment and zero sewage discharge are achieved, and the mechanical properties and environmental protection are improved.
Patent Information
- Application Number
- CN202510907387.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-09-19
AI Technical Summary
Existing baby flannel fabrics, after being finished with formaldehyde or organic halogen compounds, result in serious excess of total organic volatiles, posing a safety hazard to the production environment and the final product.
The environmentally friendly anti-soft finishing liquid is used, which contains reactive cationic polymers, bio-based cross-linking agents and nanocellulose dispersion for padding treatment. It is combined with low-temperature drying, low-temperature dyeing, supercritical CO2 fixation and biological enzyme washing floating color technology to avoid the use of formaldehyde and organic halogen compounds. A three-dimensional network skeleton is constructed through cross-linking and enzymatic hydrolysis processes to achieve a high fixation rate and zero wastewater discharge.
It achieves the goal of preventing fabric from softening under formaldehyde-free conditions, achieving total organic volatiles ≤ 50g/L, free formaldehyde ≤ 3mg/kg, color fastness to washing ≥ level 4.5, tear strength retention rate ≥ 93%, and softening rate after washing ≤ 6.5%, while achieving a high color fixation rate and zero sewage discharge.
Smart Images

Figure CN120666562A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, in particular to an environmentally friendly anti-softening treatment hot-dyeing and printing method for baby flannel fabric. Background Art
[0002] Textiles refer to flexible flat or three-dimensional structural materials formed by spinning, weaving, knitting, braiding, non-woven and other processing methods with natural or chemical fibers as basic units. They can be cut and sewn and have specific physical and chemical properties (such as breathability, strength, and elasticity). They are widely used in clothing, home textiles, industrial use and other fields. Their essential feature is that the fiber aggregate forms a stable structure through mechanical / chemical action, and has both practical functions and decorative properties. Among them, baby fleece fabric is an important branch of textiles.
[0003] In order to obtain good softening resistance and dimensional stability, existing baby flannel fabrics are usually finished with resins containing formaldehyde or organic halogen compounds. These substances inevitably release formaldehyde during the use of the fabric, which not only irritates the sensitive skin of infants and young children, but also poses a carcinogenic risk. The organic halogen compounds they contain are persistent and bioaccumulative, bringing severe ecological pollution challenges, resulting in serious exceeding of the total volatile organic compound (TVOC) standard, and posing safety risks to both the production environment and the final product. Summary of the Invention
[0004] In response to the shortcomings of the existing technology, the present invention provides an environmentally friendly anti-soft treatment, hot dyeing and printing method for baby flannel fabrics, which solves the problem that the total organic volatiles seriously exceed the standard due to the existing baby flannel fabrics being finished with resins containing formaldehyde or organic halogen compounds, and there are safety hazards in the production environment and the final product.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: an environmentally friendly anti-softening treatment hot-dyeing and printing method for baby velvet fabric, comprising the following steps:
[0006] S1: fabric pre-treatment;
[0007] S2: Padding environmentally friendly anti-softening finishing liquid: padding rate 80-85%, the environmentally friendly anti-softening finishing liquid contains a reactive cationic polymer, a bio-based cross-linking agent and a nanocellulose dispersion, the total organic volatile matter is ≤50g / L, and does not contain formaldehyde and organic halogen compounds;
[0008] S3: low temperature drying and pre-curing;
[0009] S4: heating to dyeing temperature at a rate of 1.5-2°C / min for low-temperature reactive dye dyeing;
[0010] S5: Use hot stamping transfer paper for partial printing;
[0011] S6: supercritical CO2 fixation treatment;
[0012] S7: Bio-enzyme wash for floating color.
[0013] Through the above technical solution, the water treatment system first removes large suspended solids through a multi-stage grid (pore size ≤ 5mm), then adds 0.1mol / L acid or alkaline solution to the pH adjustment tank to control the inlet pH within the range of 2.5 to 10.5 to prevent extreme pH from damaging the subsequent catalytic membrane. At the same time, PAC (15-30mg / L) and anionic PAM (0.5-1.2mg / L) are added for flocculation and sedimentation to ensure that the effluent turbidity is ≤15NTU to meet the anti-fouling requirements of the nanocatalytic membrane. In the catalytic degradation stage, TiO2 / WO3 heterojunction nanomembrane is used at a wavelength of 365nm and a power density of 30-80mW / cm 2 Under ultraviolet light, electron-hole pairs are generated, and the concentration is ≥10 -4 mol / L of ·OH free radicals; the energy regulation submodule dynamically adjusts the intensity and duration of ultraviolet irradiation by real-time monitoring of TOC and UV254 values. When the light response intensity index R>1.5, the enhanced irradiation mode is automatically started (the catalytic efficiency ηc is increased by 28%), and the reaction temperature is maintained at 35±2℃ (control accuracy ±0.5℃) through the PID temperature controller. The pH is maintained at 7.2±0.3 through conductivity feedback control. The membrane separation stage uses a 0.1μm ceramic membrane to operate under a transmembrane pressure difference of 0.15-0.35MPa. The pressure regulation submodule monitors the permeation flux degradation index online. once That is, the variable frequency pump is automatically started to increase the cross flow rate to 2.5m / s within 3 seconds; the module will also predict the critical blockage point based on historical pollution data, and issue an early warning when the pressure difference growth rate dTMP / dt>0.02MPa / min. The intelligent control module integrates PLC and edge computing units, collects 12-dimensional sensor data including ORP, UV transmittance, ion concentration, etc., and predicts the pollutant degradation path based on the long short-term memory artificial neural network (LSTM, training set error <8%). The final output error is controlled within ±5% of the optimal agent dosage (D). The regeneration maintenance module is based on the cumulative processing volume per 1000m 3 Or the flux attenuation rate exceeds 25% of the standard to start the physical-chemical synergistic online cleaning program: alternately use 40kHz ultrasonic (sound intensity 0.8W / cm 2 ) and 0.1mol / L citric acid or 0.5% NaOH solution for 30 minutes. Finally, the verification and evaluation submodule confirmed that the flux recovery rate (ηJ) ≥ 92% and the pressure difference recovery rate (ηP) ≥ 95%, and then the system was restarted. The actual operation data showed that this system could effectively clean the sample containing 200mg / L phenol and 50mg / L Cd2+ The heavy metal industrial wastewater treatment effect is outstanding: the COD removal rate exceeds 98.5%, the membrane service life is extended to 18 months (40% increase compared to conventional membranes), and the power consumption per ton of water treated is reduced to 1.8kWh (saving 62% compared to traditional processes).
[0014] Preferably, in S1, the fabric is refined with a 3 wt % tea saponin solution at 52±1° C. for 25-35 min, and then etched with a plasma treatment machine at a vacuum of 100-300 Pa and 15 kV / 200 Hz for 90±2 s.
[0015] Preferably, the reactive cationic polymer in S2 is an epoxy-modified polyurethane cationic emulsion with a hydroxyl value of 35-45 mgKOH / g and a molecular weight of 5000-10000 Da; the bio-based crosslinker is a mixture of trisodium citrate and modified chitosan with a deacetylation degree ≥85%, with a mass ratio of 2:1±0.2.
[0016] Preferably, in S2, the preparation of the nanocellulose dispersion comprises: oxidizing the microcrystalline cellulose with a TEMPO / NaBr / NaClO system, and then ultrasonically dispersing the microcrystalline cellulose at 800-1000W and 40kHz to form a dispersion having a particle size of 50-100nm, a Zeta potential of -40mV to -55mV, and a solid content of 3-5wt%, wherein the mass ratio of the dispersion to the reactive cationic polymer is 1:3-1:5.
[0017] Preferably, in S3, hot air drying is performed at 60-75° C. to a moisture content of 8±0.5%, and then pre-curing is performed at 112-118° C. for 150-180 seconds under infrared irradiation with a wavelength of 3-5 μm.
[0018] Preferably, S4 uses a vinylsulfone-containing disazobenzothiazole dye, the dyeing temperature is 43±2° C., the pH of the dye bath is controlled to 6.0-6.5 by a sodium bicarbonate-citric acid buffer system, and the dyeing time is 25 min±10%.
[0019] Preferably, the adhesive layer of the hot stamping transfer paper in S5 contains 12-15 wt% of an aqueous acrylate-silicone copolymer emulsion of silicone segments. During transfer, the pressure is applied in stages: increasing to 0.2 MPa in 0-5 s, maintaining 0.35±0.05 MPa for 5-15 s, and the temperature is 132-138°C.
[0020] Preferably, the supercritical CO2 fixation conditions in S6 are: temperature 95±2°C, pressure 22.5±0.5 MPa, time 45min±5min, CO2 flow rate 18±0.5L / min, and 1-3wt% ethanol is added to the system.
[0021] Preferably, S7 uses a thermostable laccase and lipase complex system, with an enzyme activity ratio of laccase: lipase = 1:2.5, and is enzymatically washed at 58±0.5°C and pH 5.0±0.3, with an enzyme dosage of 0.8wt% of the fabric weight.
[0022] Preferably, the baby flannel fabric obtained by the method meets the following requirements: free formaldehyde ≤ 3 mg / kg, color fastness to washing ≥ 4.5, tear strength retention rate ≥ 93%, and softening rate after washing ≤ 6.5%.
[0023] The present invention provides an environmentally friendly, anti-softening treatment, hot-dyeing, and printing method for baby flannel fabric. It has the following beneficial effects:
[0024] 1. The present invention uses an environmentally friendly anti-softening finishing liquid containing an epoxy-modified polyurethane cationic emulsion, trisodium citrate, a modified chitosan with a deacetylation degree of 85% or more, a bio-based crosslinking agent, and a nanocellulose dispersion prepared by a TEMPO oxidation method, controls the padding rate to 80-85%, and performs padding treatment under the condition of TVOC ≤ 50 g / L. The epoxy groups react with the cellulose hydroxyl groups through ring-opening, the carboxyl groups form ester bonds with the fibers to form cross-linking, and the nanocellulose fills the gaps between the fibers. The three act synergistically, and the total organic volatiles are ≤ 50 g / L. The nanocellulose does not contain formaldehyde and organic halogen compounds, thereby achieving the effect of synergistically constructing a three-dimensional network skeleton in the absence of formaldehyde, thereby preventing the fabric from softening.
[0025] 2. The present invention performs color fixation by adding 1-3 wt% ethanol co-solvent in a supercritical CO2 system at 95±2°C and 22.5±0.5 MPa for 45 min±5 min. The density of supercritical CO2 is 0.8-0.9 g / cm 3 , which promotes the dye to diffuse into the amorphous area of the fiber. Ethanol and CO2 form hydrogen bond complexes, which reduces the dipole moment of the dye and efficiently penetrates the amorphous area of the fiber. The color fixation rate reaches 98.2%, and the solvent recovery rate is 99.7%, realizing zero wastewater discharge closed-loop utilization. No organic residues are detected in the tail gas, thus achieving the effect of high color fixation rate and zero wastewater discharge.
[0026] 3. The present invention adopts a 3wt% tea saponin solution to be refined at 52±1℃ for 25-35min, and then plasma-etched for 90±2s under the conditions of 100-300Pa vacuum and 15kV / 200Hz. The hydrophobic-hydrophilic dual properties of triterpenoid saponins in the tea saponin molecule can efficiently emulsify and decompose grease impurities on the fiber surface; the plasma treatment excites 200Hz alternating discharge through a 15kV high-frequency electric field, ionizes oxygen in a low-pressure environment of 100-300Pa to produce active oxygen free radicals, and directionally etches the surface of the fabric, thereby increasing the depth of microcracks on the fiber surface to 120-150nm and reducing the contact angle from the original 103°±5° to 22°±3°, thereby achieving the effect of efficiently removing grease impurities on the fiber surface and improving the hydrophilicity of the fiber surface.
[0027] 4. The present invention adopts a high-temperature resistant composite enzyme system with an enzyme activity ratio of laccase: lipase = 1:2.5, and performs bioenzymatic washing of floating color at 58±0.5°C and pH 5.0±0.3. Laccase oxidatively decomposes the azo chromophore group of the dye through a four-electron transfer mechanism, and lipase simultaneously hydrolyzes the ester bond of the acrylate adhesive to generate a water-soluble monocarboxylic acid. The floating color removal rate is 99.3%, the residual dye is ≤0.8 mg / kg, the wastewater COD value is 86 mg / L, and BOD5 / COD = 0.51, which can be directly treated biochemically, thereby achieving an effect of achieving a floating color removal rate of ≥99% without pollution by chemical additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of an environmentally friendly anti-softening treatment hot-dyeing and printing method for baby flannel fabric proposed by the present invention. DETAILED DESCRIPTION
[0029] The following will clearly and completely describe the technical solution of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0030] Please see the attached Figure 1 The embodiment of the present invention provides an environmentally friendly anti-softening treatment and hot-dyeing and printing method for baby flannel fabric, comprising the following steps:
[0031] S1: fabric pre-treatment;
[0032] S2: Padding environmentally friendly anti-softening finishing liquid: padding rate 80-85%, the environmentally friendly anti-softening finishing liquid contains a reactive cationic polymer, a bio-based cross-linking agent and a nanocellulose dispersion, the total organic volatile matter is ≤50g / L, and does not contain formaldehyde and organic halogen compounds;
[0033] S3: low temperature drying and pre-curing;
[0034] S4: heating to dyeing temperature at a rate of 1.5-2°C / min for low-temperature reactive dye dyeing;
[0035] S5: Use hot stamping transfer paper for partial printing;
[0036] S6: supercritical CO2 fixation treatment;
[0037] S7: Bio-enzyme wash for floating color.
[0038] Specifically, first, a 3wt% tea saponin solution is refined at 52±1°C for 25-35min, and the oil impurities are efficiently removed by the emulsifying effect of tea saponin saponins. Then, the fiber is etched with a 15kV / 200Hz plasma for 90±2s at a vacuum of 100-300Pa, and the active oxygen free radicals generated by high-frequency discharge are used to increase the hydrophilicity of the fiber surface by more than 80%. Subsequently, an environmentally friendly anti-softening finishing liquid containing an epoxy-modified polyurethane cationic emulsion, trisodium citrate and a modified chitosan with a deacetylation degree ≥85% as a bio-based cross-linking agent, and a nanocellulose dispersion with a Zeta potential of -40mV to -55mV prepared by a TEMPO oxidation method is used for padding, and the padding rate is controlled to be 80-85%. The epoxy groups react with the hydroxyl groups of cellulose to form an ester bond cross-linking, the carboxyl groups form ester bonds with the fibers, and the nanocellulose fills the gaps between the fibers. The three cooperate to construct an aldehyde-free three-dimensional network skeleton under the condition of TVOC≤50g / L. Then, the fiber is subjected to infrared spectroscopy at a wavelength of 3-5μm. External irradiation pre-curing at 112-118 ° C for 150-180s to achieve deep reaction of the crosslinker and reduce energy consumption by 40%; then the temperature is increased to 43 ± 2 ° C at a gradient of 1.5-2 ° C / min, and a sodium bicarbonate-citric acid buffer system is used to maintain pH 6.0-6.5. The low-temperature reactive dye containing vinyl sulfone group is dyed for 25min ± 10%, so that the dye uptake reaches 92%; then the water with 12-15wt% of the silicone chain is used. The acrylate-silicone copolymer adhesive was pressurized in sections at 132-138°C for 0-5s, increasing the pressure to 0.2MPa and maintaining it at 0.35±0.05MPa for 5-15s to achieve close adhesion of the hot stamping foil to the complex suede surface; further, in a supercritical CO2 system with 1-3wt% ethanol as a co-solvent, it was treated at 95±2°C and 22.5±0.5MPa for 45min±5min, with a density of 0.8-0.9g / cm 3 The supercritical state promotes the diffusion of dyes into the amorphous area of the fiber, achieving a 98% fixation rate and zero wastewater discharge; finally, a high-temperature resistant composite enzyme system with an enzyme activity ratio of laccase: lipase = 1:2.5 is used to decompose unfixed dyes at 58±0.5℃ and pH5.0±0.3. The laccase oxidizes the chromogenic group and the lipase degrades the adhesive residue, achieving a floating color removal rate of ≥99% and no chemical additive pollution.
[0039] See attached Figure 1 In S1, the fabric is refined with a 3 wt % tea saponin solution at 52 ± 1 °C for 25-35 min, and then etched by a plasma treatment machine at a vacuum degree of 100-300 Pa and 15 kV / 200 Hz for 90 ± 2 s.
[0040] Specifically, a 3wt% tea saponin solution was used to refine the fabric at a constant temperature of 52±1°C for 25-35 minutes. The hydrophobic and hydrophilic properties of the triterpenoid saponins in the tea saponin molecules were used to efficiently emulsify and decompose the grease impurities on the fiber surface. The fabric was then transferred to a vacuum plasma treatment machine, where a 15kV high-frequency electric field excited a 200Hz alternating discharge, ionizing oxygen in a low-pressure environment of 100-300Pa to produce reactive oxygen free radicals (O2 - , OH), and the surface of the fabric was directionally etched for 90±2s, which increased the depth of the microcracks on the fiber surface to 120-150nm, reduced the contact angle from the original 103°±5° to 22°±3°, and improved the hydrophilicity by more than 80%.
[0041] See attached Figure 1 The reactive cationic polymer in S2 is an epoxy-modified polyurethane cationic emulsion with a hydroxyl value of 35-45 mgKOH / g and a molecular weight of 5000-10000 Da; the bio-based cross-linking agent is a mixture of trisodium citrate and modified chitosan with a deacetylation degree ≥85%, with a compound mass ratio of 2:1±0.2.
[0042] Specifically, microcrystalline cellulose is selectively oxidized by introducing it into a catalytic system consisting of a 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) catalyst, a sodium bromide co-catalyst, and a sodium hypochlorite oxidant. The cellulose glucose unit is converted into a carboxyl sodium salt structure through a TEMPO-mediated directed oxidation reaction of C6 primary hydroxyl groups. The oxidized product is treated in an ultrasonic field with a power of 800-1000W and a fixed frequency of 40kHz for 30 minutes. The cavitation effect generates an instantaneous local pressure exceeding 10,000atm, effectively dissociating hydrogen bond bundles and controlling the nanofiber particle size within the range of 50-100nm. The resulting dispersion is in a stable sol state with a zeta potential stable in the range of -40mV to -55mV. The double-layer repulsion formed by the ionization of surface carboxyl groups ensures a storage period of ≥90 days at a solid content of 3-5wt%. The dispersion is compounded with an epoxy-modified polyurethane cationic emulsion with a hydroxyl value of 35-45mgKOH / g in a mass ratio of 1:3 to 1:5 for application.
[0043] See attached Figure 1In S2, the preparation of the nanocellulose dispersion includes: oxidizing the microcrystalline cellulose with a TEMPO / NaBr / NaClO system, and then ultrasonically dispersing the microcrystalline cellulose at 800-1000 W and 40 kHz to form a dispersion with a particle size of 50-100 nm, a zeta potential of -40 mV to -55 mV, and a solid content of 3-5 wt%, and the mass ratio of the microcrystalline cellulose to the reactive cationic polymer is 1:3-1:5.
[0044] Specifically, microcrystalline cellulose is selectively oxidized by introducing it into a catalytic system consisting of a 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) catalyst, a sodium bromide co-catalyst, and a sodium hypochlorite oxidant. The cellulose glucose unit is converted into a carboxyl sodium salt structure through a TEMPO-mediated directed oxidation reaction of C6 primary hydroxyl groups. The oxidized product is treated in an ultrasonic field with a power of 800-1000W and a fixed frequency of 40kHz for 30 minutes. The cavitation effect generates an instantaneous local pressure exceeding 10,000atm, effectively dissociating hydrogen bond bundles and controlling the nanofiber particle size within the range of 50-100nm. The resulting dispersion is in a stable sol state with a zeta potential stable in the range of -40mV to -55mV. The double-layer repulsion formed by the ionization of surface carboxyl groups ensures a storage period of ≥90 days at a solid content of 3-5wt%. The dispersion is compounded with an epoxy-modified polyurethane cationic emulsion with a hydroxyl value of 35-45mgKOH / g in a mass ratio of 1:3 to 1:5 for application.
[0045] See attached Figure 1 In S3, hot air drying is performed at 60-75°C to a moisture content of 8±0.5%, and then pre-curing is performed at 112-118°C for 150-180s under infrared irradiation with a wavelength of 3-5μm.
[0046] Specifically, the temperature is gradually increased in the range of 60-75℃ in a circulating hot air oven, and the moisture content of the fabric is accurately reduced to the critical state of 8.0±0.5% by controlling the wind speed of the penetrating airflow at 1.2±0.1m / s. Then, the fabric is irradiated with a 3-5μm wavelength mid-infrared band device and directional pre-cured for 150-180s under an effective heat field of 112-118℃. The spectral energy of this band is combined with the stretching vibration frequency of the OH bond of the cellulose molecule (3100-3500cm -1 )’s resonance absorption effect promotes the deep penetration reaction of the cross-linking agent.
[0047] See attached Figure 1 S4 uses vinylsulfone-containing disazobenzothiazole dyes, the dyeing temperature is 43±2℃, the dye bath pH is controlled at 6.0-6.5 by a sodium bicarbonate-citric acid buffer system, and the dyeing time is 25min±10%.
[0048] Specifically, by using a disazobenzothiazole low-temperature dye containing a vinylsulfone active group, the dyeing process is carried out at a dyeing temperature of 43±2°C, and the pH value of the dye bath is stably controlled in a slightly acidic window of 6.0-6.5 by adding a sodium bicarbonate-citric acid buffer system. The target temperature is reached at a gradient heating rate of 1.5-2°C / min and maintained for a dyeing cycle of 25min±2.5min.
[0049] See attached Figure 1 The adhesive layer of the hot stamping transfer paper in S5 contains a water-based acrylate-silicone copolymer emulsion with 12-15wt% silicone segments. The pressure is applied in stages during transfer: rising to 0.2MPa in 0-5s, maintaining 0.35±0.05MPa for 5-15s, and the temperature is 132-138°C.
[0050] Specifically, the adhesive layer of the hot stamping transfer paper is constructed by using a water-based acrylate-silicone copolymer emulsion containing 12-15wt% of silicone segments. When the silicone content is lower than 12%, the surface tension is greater than 35mN / m, resulting in incomplete velvet coverage; when it is higher than 15%, the peel strength is less than 1.2N / cm. The adhesive is set to melt and flow in the hot pressing range of 132-138℃, corresponding to a melt index of 5.3-7.8g / 10min; during transfer, the pressure is gradually increased to 0.2MPa from 0-5 seconds to prevent the hot stamping foil from shifting (shear rate ≤15s -1 ), then maintain a main pressure of 0.35±0.05MPa for 5-15 seconds to allow the melt to penetrate into the fiber bundle to a depth of 80-120μm, and use the silicone chain segment to migrate to the interface to form a 22mN / m low-energy barrier layer to inhibit phase separation. At the same time, the acrylic ester chain segment plasticizes and penetrates into the amorphous area of the fiber to form a mechanical anchor, ensuring a transfer accuracy of 120 lines / cm, 20 water washings and a peeling loss rate of <3%, a production line speed of 18m / min, an energy consumption of 0.11kW·h / ㎡, and a VOC emission of 3.2μg / g, which meets the limit value of GB / T33352.
[0051] See attached Figure 1 The supercritical CO2 fixation conditions in S6 are: temperature 95±2℃, pressure 22.5±0.5MPa, time 45min±5min, CO2 flow rate 18±0.5L / min, and 1-3wt% ethanol is added to the system.
[0052] Specifically, since the dye solubility drops sharply by 30% when the temperature is lower than 93°C, resulting in uneven color fixation, and the fiber thermal damage is accelerated when the temperature is higher than 97°C, the color fixation treatment is carried out in a CO2 environment with a temperature of 95±2°C and a pressure of 22.5±0.5MPa. The CO2 flow rate is regulated by a mass flow meter to 18±0.5L / min for 45min±5min, and 1-3wt% ethanol is added as a co-solvent; the pressure accuracy is ±0.5MPa to ensure that the CO2 density is stable at 0.85g / cm3 The dye diffusion coefficient reaches 4.7×10 -9 m 2 / s, and a flow rate of 18L / min ensures that the turbulent state of Re>4000 eliminates mass transfer resistance. When the ethanol addition amount is less than 1wt%, the polar dye is insufficiently dissolved, while higher than 3wt% causes fiber swelling and damage. In terms of reaction mechanism, ethanol and CO2 form hydrogen bond complexes, which causes the dye dipole moment to decrease from 2.1D to 1.3D and efficiently penetrate the amorphous region of the fiber. ITS testing (report EC-2024-7738) shows: the color fixation rate reaches 98.2%, the water washing color fastness is level 5 (ISO105-C06), the energy consumption is 0.8kW·h / kg, which saves 62%, and the solvent recovery rate is 99.7%, achieving zero wastewater discharge closed-loop utilization, and no organic residues are detected in the exhaust gas (FTIR detection limit is 0.1ppm).
[0053] See attached Figure 1 S7 uses a thermostable laccase and lipase complex system with an enzyme activity ratio of laccase: lipase = 1:2.5, and is enzymatically washed at 58±0.5℃ and pH 5.0±0.3. The enzyme dosage is 0.8wt% of the fabric weight.
[0054] Specifically, by using thermostable laccase and lipase in an enzyme activity ratio of 1:2.5, since the half-life of laccase is less than 5 minutes when it exceeds 60°C and the catalytic efficiency of lipase decreases by 30% below 55°C, the enzyme washing temperature is controlled at 58±0.5°C to form a synergistic window, and the pH value of citric acid-disodium hydrogen phosphate buffer is maintained at 5.0±0.3 to keep the laccase specific activity above 85% (ABTS method), and the interfacial activation energy of lipase is reduced to 42 kJ / mol. The Langmuir adsorption saturation threshold (fitting R 2 =0.993). Within a treatment time of 20±2 minutes, laccase oxidatively decomposes the dye's azo chromophore group via a four-electron transfer mechanism (oxidation potential of +780 mV), while lipase simultaneously hydrolyzes the ester bond of the acrylate adhesive to form a water-soluble monocarboxylic acid. Testing confirmed: a floating color removal rate of 99.3% (whiteness method), residual dye ≤0.8 mg / kg (HPLC-MS), a wastewater COD value of 86 mg / L and a BOD5 / COD ratio of 0.51, enabling direct biochemical treatment, a cellulose polymerization degree retention of 98.5% (copper ethylenediamine method), a cloth surface pH of 6.8±0.2 (GB / T7573), and 82% enzyme activity retention after five cycles, further saving unit costs.
[0055] See attached Figure 1 The baby flannel fabric obtained by this method meets the following requirements: free formaldehyde ≤ 3 mg / kg, color fastness to washing ≥ level 4.5, tear strength retention rate ≥ 93%, and softening rate of hand feel after washing ≤ 6.5%.
[0056] Specifically, S2 adopts epoxy modified polyurethane / citric acid-chitosan formaldehyde-free cross-linking system to replace traditional formaldehyde-containing resin, which makes the free formaldehyde content of baby velvet fabric ≤3mg / kg; and the synergistic effect of supercritical CO2 fixation in S6 and laccase-lipase compound enzyme washing in S7 makes the fabric's color fastness to washing reach ≥4.5 level (GB / T3921-2008); 112-118℃ low-temperature pre-curing in S3 protects fiber crystallinity (XRD crystallinity retention rate 98.2%) and S2 nanocellulose (addition amount 1:3-1:5) physically enhances the fiber gap, making the tear strength retention rate ≥93% (GB / T3917.2-2009); due to the lasting flexibility given by the composite cross-linking network of trisodium citrate and chitosan, the softening rate of the velvet fabric after washing is ≤6.5%.
[0057] Example 1:
[0058] Optimized ingredients:
[0059] Bio-based cross-linker: trisodium citrate: modified chitosan = 2.2:1;
[0060] Nanocellulose dispersion: solid content 4.5 wt%, zeta potential -50 mV;
[0061] Nanocellulose / cationic emulsion mass ratio: 1:3.
[0062] Preparation process:
[0063] S1: The baby fleece fabric was immersed in a 3wt% tea saponin solution and treated in a constant temperature water bath at 52°C for 30 minutes to remove grease from the fiber surface through the emulsification effect of tea saponin triterpenoid saponins (grease removal rate ≥ 98%); the fabric was rinsed with 40°C soft water until it was neutral (conductivity ≤ 5μS / cm); the fabric was transferred to a vacuum plasma processor, evacuated to 200Pa, and oxygen was introduced. A voltage of 15kV and an alternating electric field of 200Hz were applied for etching for 90 seconds to generate microcracks (depth 120-150nm) on the fiber surface, and the contact angle decreased from 103° to 22°;
[0064] S2: padding rate 82%, finishing solution contains epoxy-modified polyurethane, bio-based crosslinker and nanocellulose dispersion;
[0065] S3: Dry in a circulating hot air oven at 70°C and a wind speed of 1.2 m / s with penetrating airflow. Monitor the moisture content in real time until it reaches 8.0±0.5% (online feedback from an infrared moisture meter). Immediately transfer to a mid-infrared radiation device (dominant wavelength 4 μm) and irradiate at 115°C for 165 seconds. The infrared energy resonates with the OH bond of cellulose (3100-3500 cm -1 ) Promote deep reaction of cross-linking agent;
[0066] S4: Add vinylsulfone-containing disazobenzothiazole dye to the jigger, adjust the pH to 6.2 with a sodium bicarbonate-citric acid buffer system, raise the temperature to 43°C at a rate of 1.8°C / min (PID temperature control accuracy ±0.3°C), and dye at this temperature for 25 minutes. Dye uptake is >92%.
[0067] S5: Cover the fabric surface with hot stamping transfer paper; Stage 1: At 135°C, increase the pressure linearly to 0.2 MPa within 4 seconds (shear rate ≤ 15s -1 ) to prevent the hot stamping foil from shifting; Stage 2: Maintain a pressure of 0.35 MPa for 10 seconds to allow the adhesive melt to penetrate the fiber bundle to a depth of 80-120 μm (melt index 6.5 g / 10 min);
[0068] S6: The dyed fabric was placed in a supercritical reactor and 2 wt% ethanol (relative to the mass of CO2) was added. The reaction was maintained for 45 minutes. The dye diffusion coefficient reached 4.7×10 -9 m 2 / s, fixation rate 98.5%;
[0069] S7: A laccase:lipase ratio of 1:2.5 (enzyme activity ratio) was added to a citric acid-disodium hydrogen phosphate buffer (pH 5.0). The mixture was then treated in a 58°C shaking water bath (amplitude 120 rpm) for 20 minutes. The enzyme dosage was 0.8% of the fabric weight. The enzyme was then inactivated in 80°C hot water for 5 minutes. The floating color removal rate was 99.3%.
[0070] Performance testing:
[0071] Tear strength retention rate: ISO13937-2:2000 (tear strength by trapezoidal method);
[0072] Color fastness to washing: AATCC61-2020;
[0073] Free formaldehyde: GB / T2912.1-2009 (water extraction method).
[0074] Control group 1:
[0075] Element:
[0076] The nanocellulose dispersion was omitted, and the rest was the same as in Example 1;
[0077] Preparation process:
[0078] No nanocellulose was added in S2, and the rest was the same as in Example 1;
[0079] Performance testing:
[0080] The same as in Example 1.
[0081] Performance comparison table 1:
[0082] Test items Control group 1 Example 1 in conclusion Tear strength retention rate 86% 95% Nanocellulose improves 9% Color fastness to washing Level 4 Level 5 The cross-linked network is denser Free formaldehyde 2.3 mg / kg 1.6 mg / kg Nanocellulose adsorption residue
[0083] Conclusion: Nanocellulose improves mechanical strength and color fastness by filling fiber gaps (cracks with a depth of 120-150 nm) and physical cross-linking.
[0084] Example 2:
[0085] Optimized ingredients:
[0086] Bio-based cross-linker: trisodium citrate: modified chitosan = 1.8:1 (increases chitosan flexibility);
[0087] Adhesive silicone content: 15wt%.
[0088] Preparation process:
[0089] S5: A water-based acrylate-silicone copolymer emulsion is used as the adhesive layer, in which the silicone segment accounts for 15wt%.
[0090] Performance testing:
[0091] Hand softening rate: ISO17299-3:2014 (Quantitative method for sensory softening of fabrics);
[0092] Hot stamping bonding strength: ENISO11339:2010 (T-peel method);
[0093] Bending stiffness: ASTM D1388-18 (cantilever beam method).
[0094] Control group 2:
[0095] Element:
[0096] S2 was replaced with a finishing solution containing formaldehyde resin (2D resin);
[0097] Preparation process:
[0098] S2 uses 2D resin (formaldehyde emission 82 mg / kg), and the rest is the same as Example 2.
[0099] Performance testing:
[0100] The same as the second embodiment.
[0101] Performance comparison table:
[0102]
[0103] Conclusion: The citric acid-chitosan cross-linking system completely eliminates the hazard of formaldehyde while maintaining mechanical properties.
[0104] Example 3:
[0105] Optimized ingredients:
[0106] S6 adds 3 wt% ethanol as a co-solvent, and the dye is a benzothiazole dye containing a bisvinyl sulfone group.
[0107] Preparation process:
[0108] S6: supercritical CO2 fixation (97°C / 22.5MPa), 3wt% ethanol, flow rate 18.5L / min. Others are the same as in Example 1.
[0109] Performance testing:
[0110] Color fastness: AATCC61-2020 (color fastness to washing: accelerated method);
[0111] Wastewater salt content: EPA300.0 (ion chromatography method).
[0112] Control group three:
[0113] Preparation process:
[0114] S6 was changed to traditional steam fixation (102°C / 30min, containing sodium sulfate), and the rest was the same as in Example 3.
[0115] Performance comparison table 3:
[0116] Test items Control group three Example 3 in conclusion Fixation rate 84% 28g / L <![CDATA[Improvement of Supercritical CO2 Diffusion Depth]]> Wastewater salinity 28g / L 3g / L Save water treatment costs
[0117] Conclusion: Supercritical CO2 at 0.85g / cm 3 The dye diffusion coefficient is increased to 4.7×10 -9 m 2 / s, achieving high color fixation and saving water treatment costs.
[0118] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. An environmentally friendly anti-softening treatment hot-dyeing and printing method for baby velvet fabric, characterized in that: The following steps are involved: S1: fabric pre-treatment; S2: Padding environmentally friendly anti-softening finishing liquid: padding rate 80-85%, the environmentally friendly anti-softening finishing liquid contains a reactive cationic polymer, a bio-based cross-linking agent and a nanocellulose dispersion, the total organic volatile matter is ≤50g / L, and does not contain formaldehyde and organic halogen compounds; S3: low temperature drying and pre-curing; S4: heating to dyeing temperature at a rate of 1.5-2°C / min for low-temperature reactive dye dyeing; S5: Use hot stamping transfer paper for partial printing; S6: supercritical CO2 fixation treatment; S7: Bio-enzyme wash for floating color.
2. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: In S1, the fabric is refined with a 3 wt % tea saponin solution at 52±1° C. for 25-35 min, and then etched with a plasma treatment machine at a vacuum of 100-300 Pa and 15 kV / 200 Hz for 90±2 s.
3. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: The reactive cationic polymer in S2 is an epoxy-modified polyurethane cationic emulsion with a hydroxyl value of 35-45 mgKOH / g and a molecular weight of 5000-10000 Da; the bio-based cross-linking agent is a mixture of trisodium citrate and modified chitosan with a deacetylation degree ≥85%, with a mass ratio of 2:1±0.
2.
4. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: In S2, the preparation of the nanocellulose dispersion includes: oxidizing the microcrystalline cellulose with a TEMPO / NaBr / NaClO system, and then ultrasonically dispersing the microcrystalline cellulose at 800-1000 W and 40 kHz to form a dispersion with a particle size of 50-100 nm, a zeta potential of -40 mV to -55 mV, and a solid content of 3-5 wt%, wherein the mass ratio of the microcrystalline cellulose to the reactive cationic polymer is 1:3-1:
5.
5. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: In S3, the film is dried with hot air at 60-75° C. to a moisture content of 8±0.5%, and then pre-cured at 112-118° C. for 150-180 seconds under infrared irradiation with a wavelength of 3-5 μm.
6. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: S4 uses vinylsulfone-containing disazobenzothiazole dyes, the dyeing temperature is 43±2°C, the dye bath pH is controlled at 6.0-6.5 by a sodium bicarbonate-citric acid buffer system, and the dyeing time is 25min±10%.
7. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: The adhesive layer of the hot stamping transfer paper in S5 contains a water-based acrylate-silicone copolymer emulsion with 12-15 wt% silicone segments. During transfer, the pressure is applied in stages: increasing to 0.2 MPa in 0-5 seconds, maintaining 0.35±0.05 MPa for 5-15 seconds, and the temperature is 132-138°C.
8. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: The supercritical CO2 fixation conditions in S6 are: temperature 95±2°C, pressure 22.5±0.5MPa, time 45min±5min, CO2 flow rate 18±0.5L / min, and 1-3wt% ethanol is added to the system.
9. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: S7 uses a thermostable laccase and lipase complex system with an enzyme activity ratio of laccase: lipase = 1:2.
5. It is washed at 58±0.5℃ and pH 5.0±0.3, and the enzyme dosage is 0.8wt% of the fabric weight.
10. The environmentally friendly anti-softening treatment hot-dyeing and printing method for baby fleece fabric according to claim 1, characterized in that: The baby flannel fabric obtained by the method meets the following requirements: free formaldehyde ≤ 3 mg / kg, color fastness to washing ≥ level 4.5, tear strength retention rate ≥ 93%, and hand softening rate after washing ≤ 6.5%.